Analysis of HOTS-Based Economic Learning: Case Study on Vocational High School Students in Minahasa Regency - Manongko, Allen A. Ch.; Sinoritha, Julia; Wantah, Edwin; Taroreh, Johny; Wuisang, Jerry RH (International Journal of Multidisciplinary Approach Research and Science, 2025)
This study aims to analyze the implementation of Higher Order Thinking Skills (HOTS)-based economic learning for Vocational High School (SMK) students in Minahasa Regency. The focus of the study includes teachers' understanding of the HOTS concept, the learning strategies applied, the forms of evaluation used, and the factors that inhibit the implementation of HOTS in the learning process. The method used is a qualitative approach with data collection techniques through in-depth interviews, classroom observations, and documentation of evaluation questions. The results of the study indicate that most teachers do not fully understand the HOTS concept, which has an impact on the low implementation of learning strategies based on analysis, evaluation, and creation. Learning evaluation is still dominated by low cognitive level questions (C1–C2), while HOTS-based questions are still minimal. Factors inhibiting HOTS implementation include time constraints, lack of training, inadequate learning facilities, and low student learning motivation. This study recommends the need for HOTS question preparation training, provision of educational technology facilities, and systemic support from school management to encourage more contextual economic learning and be able to develop students' critical thinking skills.